2x-3=1then value of x is
Attachments:
![](https://hi-static.z-dn.net/files/d6e/b4b6e9cc28fcde468cff6083972b703f.jpg)
Answers
Answered by
1
Given Equation is 2^x-3 = 1.
Apply log on both sides, we get
log(2^x-3) = log 1
We know that log(x^b) = b.log(x)
(x - 3)log 2 = log 1
We know that log 1 = 0
(x - 3) log 2 = 0
(x - 3) = 0/log 2
x - 3 = 0
x = 3.
Hope this helps!
Apply log on both sides, we get
log(2^x-3) = log 1
We know that log(x^b) = b.log(x)
(x - 3)log 2 = log 1
We know that log 1 = 0
(x - 3) log 2 = 0
(x - 3) = 0/log 2
x - 3 = 0
x = 3.
Hope this helps!
siddhartharao77:
If possible brainliest it
Similar questions